With regard to the conventional use of ocitocitos postpartum - Carbonel Holguin, Juan (2015)
In 200 normal women in post partum a comparative study of the effects of ergonovine was made; half of the patients were controls and did not receive the drug; half of them received 0.2 mg. of ergonovine maleate i.m. immediately after expulsion of the placenta and the some amount every 6 hours per os; no significant difference was observed between both groups nor in the loss blood, neither in the uterine involution or muscle tone. On this basis the authors discuss the value of the routine administration of this type of drug s in the normal puerperium.